Raloxifene, a cannabinoid type-2 receptor inverse agonist, mitigates visual deficits and pathology and modulates microglia after ocular blast. (May 2022) - Honig, Marcia G.; Del Mar, Nobel A.; Henderson, Desmond L.; O'Neal, Dylan; Yammanur, Meghna; Cox, Rachel; Li, Chunyan; Perry, Aaron M.; Moore, Bob M.; Reiner, Anton
Abstract: Visual deficits after ocular blast injury (OBI) are common, but pharmacological approaches to improve long-term outcomes have not been identified. Blast forces frequently damage the retina and optic nerves, and work on experimental animals has shown the pro-inflammatory actions of microglia can further exacerbate such injuries. Cannabinoid type-2 receptor (CB2) inverse agonists specifically target activated microglia, biasing them away from the harmful pro-inflammatory M1 state toward the helpful reparative M2 state. We previously found that treating mice with CB2 inverse agonists after traumatic brain injury, produced by either focal cranial air blast or dorsal cranial impact, greatly attenuated the visual deficits and pathology that otherwise resulted. Here we examined the consequences of single and repeat OBI and the benefit provided by raloxifene, an FDA-approved estrogen receptor drug that possesses noteworthy CB2 inverse agonism. After single OBI, although the amplitudes of the A- and B-waves of the electroretinogram and pupil light response appeared to be normal, the mice showed hints of deficits in contrast sensitivity and visual acuity, a trend toward optic nerve axon loss, and significantly increased light aversion, which were reversed by 2 weeks of daily treatment with raloxifene. Mice subjected to repeat OBI (5 blasts spaced 1 min apart), exhibited more severe visual deficits, including decreases in contrast sensitivity, visual acuity, the amplitudes of the A- and B-waves of the electroretinogram, light aversion, and resting pupil diameter (i.e. hyperconstriction), accompanied by the loss of photoreceptor cells and optic nerve axons, nearly all of which were mitigated by raloxifene. Interestingly, optic nerve axon abundance was strongly correlated with contrast sensitivity and visual acuity across all groups of experimental mice in the repeat OBI study, suggesting optic nerve axon loss with repeat OBI and its attenuation with raloxifene are associated with the extent of these two deficits while photoreceptor abundance was highly correlated with A-wave amplitude and resting pupil size, suggesting a prominent role for photoreceptors in these two deficits. Quantitative PCR (qPCR) showed levels of M1-type microglial markers (e.g. iNOS, IL1β, TNFα, and CD32) in retina, optic nerve, and thalamus were increased 3 days after repeat OBI. With raloxifene treatment, the overall expression of M1 markers was more similar to that in sham mice. Raloxifene treatment was also associated with the elevation of IL10 transcripts in all three tissues compared to repeat OBI alone, but the results for the three other M2 microglial markers we examined were more varied. Taken together, the qPCR results suggest that raloxifene benefit for visual function and pathology was associated with a lessening of the pro-inflammatory actions of microglia. The benefit we find for raloxifene following OBI provides a strong basis for phase-2 efficacy testing in human clinical trials for treating ocular injury. Highlights: Repeat OBI in mice causes visual deficits and loss of photoreceptors and RGC axons. Raloxifene is an FDA-approved SERM that also exhibits CB2 inverse agonism. Raloxifene reduces visual system damage and rescues photoreceptor cells after OBI. Raloxifene lessens the pro-inflammatory actions of microglia after repeat OBI. Raloxifene benefit for OBI supports its phase-2 testing as a therapy for eye trauma.